2022
DOI: 10.1007/s00068-022-01978-z
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic, trauma surgery, and Covid-2019 pandemic: clinical panorama and future prospective in Europe

Abstract: Purpose This study investigated the impact of the Covid-19 pandemic in Europe on consultations, surgeries, and traumas in the field of orthopaedic and trauma surgery. Strategies to resume the clinical activities were also discussed. Methods This systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses: the 2020 PRISMA statement. All the comparative studies reporting data on the impact of Covid-19 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 120 publications
(176 reference statements)
1
5
0
Order By: Relevance
“…This was in accordance with a study done in Europe, which conducted a systematic review and revealed that many studies show a decrease in orthopedic consultations, which decreased between 20.9 and 90.1%. Seven studies evaluated the number of emergency and trauma consultations, which decreased between 37.7 and 74.2% [ 12 ]. Also, the Al-Khobar study reported that in the pre-COVID-19 period, the average discharge time was 18.90 ±12.74 days, and during the COVID-19 period, the average discharge time was 4.28 ± 3.52 days [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was in accordance with a study done in Europe, which conducted a systematic review and revealed that many studies show a decrease in orthopedic consultations, which decreased between 20.9 and 90.1%. Seven studies evaluated the number of emergency and trauma consultations, which decreased between 37.7 and 74.2% [ 12 ]. Also, the Al-Khobar study reported that in the pre-COVID-19 period, the average discharge time was 18.90 ±12.74 days, and during the COVID-19 period, the average discharge time was 4.28 ± 3.52 days [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other coronaviruses caused epidemics in the past decades, including Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS) [ 3 , 4 ]. The COVID-19 pandemic imposed healthcare systems worldwide with new challenges and considerable organisational efforts [ 5 10 ]. Often far-reaching process changes, such as the management of patient flows, had to be implemented in everyday clinical practice within a very short period [ 11 – 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported a change in trauma epidemiology influenced by the imposed restrictions. A significant decrease in trauma admissions during the COVID-19 lockdown was found [5][6][7][8]. Differences in the most common injury mechanism and mean age were observed during COVID-19 compared to the same period in previous years [9][10][11].…”
Section: Introductionmentioning
confidence: 99%